2021 International Conference on Decision Aid Sciences and Application (DASA) 2021
DOI: 10.1109/dasa53625.2021.9682366
|View full text |Cite
|
Sign up to set email alerts
|

QoE Modeling Associated with QoS Impairment Parameters in 5G Networks Using AHP Decision Making Technique

Abstract: This paper aims to propose the Quality of Experience (QoE) models based on the expectation and/or the perception of 5G users to evaluate for Mean Opinion Score (MOS) for real-time or interactive services/applications with high reliability. Therefore, based on the fundamental QoE concept, the Analytic Hierarchy Process (AHP) decision making technique has been applied. Seven participants or evaluators were recruited for the interview remotely via phone calls. From the analysis using AHP technique, the coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The AHP method is very useful in all areas. Hence, it is important to know which method of calculation is accurate in order to set the right order of criteria [31]. Another study reported that the inconsistency in judgment and hence in the pairwise comparison matrix of the AHP is the most significant issue to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The AHP method is very useful in all areas. Hence, it is important to know which method of calculation is accurate in order to set the right order of criteria [31]. Another study reported that the inconsistency in judgment and hence in the pairwise comparison matrix of the AHP is the most significant issue to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to know which method for calculation is accurate in order to set right order of criteria. [27] Another research reported that inconsistency in judgment and hence in pairwise comparison matrix of the AHP is the most significant issue to be addressed. Besides, analytical hierarchy processing has been widely applied on various case studies and numerous applications.…”
Section: Discussionmentioning
confidence: 99%
“…28 Then, the network has to be considered. 31 The key outcome of a systems engineering process based on AHP is learning that occurs from the decisions. Some decisions may not work well -consequently, these can be re-modeled by changing criteria and weights.…”
Section: Zero Trust Security Criteriamentioning
confidence: 99%